Motivasi Belajar Bahasa Arab (Studi Kasus Mahasiswa PBA IAIN Palangkaraya 2017/2018) - Rahman, Nur Fuadi (Universitas Islam Negeri Raden Intan Lampung, 2018)
Abstract: There are two types of motivations in learning second language; integrative motivation and instrumental motivation. Integrative motivation require of positiveness from students to native speaker and culture. Instrumental motivation is a feeling of language learner that they need to learn second language to get something important in their lives. In the 2017/2018 IAIN Palangka Raya had 928 students, and only 24 students choose PBA as program study. This was attracts researcher to see the motivation of PBA students in learning Arabic language from the perspective of Gardner’s motivational theory. Researcher was also looking for the factors that affect the motivational. This research was use qualitative method and case study was chosen. The results showed that 42% students had integrative motivational in learned Arabic language, and the rest had 58% of instrument motivational. One of the influence factors was student’s educational background.Keywords:Arabic language, Gardner, Instrumental motivation, Integrative motivation